Development of a device for determining work electron output - Makeeva, O.V.; Oleshko, V.S.; Fedorov, A.V.; Yurov, V.M. (KU publ., 2020)
The surface is the most important component of metal parts and it is necessary to control its condition at all stages of the life cycle of the part - during its production, operation and repair. To carry out reliable non-destructive testing of metal parts, specially developed tools and methods for its use are necessary. The measuring electrode of the sensor of the measuring device of the contact potential difference and the surface of the metal part to be controlled form a capacitor, between the plates of which the contact potential difference occurs. The sensor of the device is a kind of intermediary between the contact potential difference and the measuring circuit. The portable complex for measuring the contact potential difference developed by the authors on the basis of a portable digital oscilloscope allows non-destructive testing of the surface of metal parts during their production, operation or repair to be performed continuously.
Электрондардың шығу жұмысын анықтайтын құрылғы әзірлеу.
Разработка устройства определения работы выхода электронов.
Keywords: non-destructive testing; metal part; surface; capacitor; contact potential difference